Brain structure and neurocognitive function in two professional mountaineers during 35 days of severe normobaric hypoxia. (30th June 2022) - Sönksen, Sven‐Erik; Kühn, Sven; Basner, Mathias; Gerlach, Darius; Hoffmann, Fabian; Mühl, Christian; Tank, Jens; Noblé, Hans‐Jürgen; Akgün, Katja; Ziemssen, Tjalf; Jordan, Jens; Limper, Ulrich
Abstract: Background and purpose: Animal studies suggest that exposure to severe ambient hypoxia for several days may have beneficial long‐term effects on neurodegenerative diseases. Because, the acute risks of exposing human beings to prolonged severe hypoxia on brain structure and function are uncertain, we conducted a pilot study in healthy persons. Methods: We included two professional mountaineers (participants A and B) in a 35‐day study comprising an acclimatization period and 14 consecutive days with oxygen concentrations between 8% and 8.8%. They underwent cerebral magnetic resonance imaging at seven time points and a cognitive test battery covering a spectrum of cognitive domains at 27 time points. We analysed blood neuron specific enolase and neurofilament light chain levels before, during, and after hypoxia. Results: In hypoxia, white matter volumes increased (maximum: A, 4.3% ± 0.9%; B, 4.5% ± 1.9%) whilst gray matter volumes (A, −1.5% ± 0.8%; B, −2.5% ± 0.9%) and cerebrospinal fluid volumes (A, −2.7% ± 2.4%; B, −5.9% ± 8.2%) decreased. Furthermore, the number (A, 11–17; B, 26–126) and volumes (A, 140%; B, 285%) of white matter hyperintensities increased in hypoxia but had returned to baseline after a 3.5‐month recovery phase. Diffusion weighted imaging of the white matter indicated cytotoxic edema formation. We did not observe changes in cognitive performance or biochemical brain injury markers. Discussion: In highly selected healthy individuals, severe sustained normobaric hypoxia over 2 weeks elicited reversible changes in brain morphology without clinically relevant changes in cognitive function or brain injury markers. The finding may pave the way for future translational studies assessing the therapeutic potential of hypoxia in neurodegenerative diseases. Abstract : To investigate the safety of hypoxia on cognitive performance and cerebral morphology, two professional mountaineers were exposed for 14 consecutive days to oxygen concentrations of approximately 8.8%. The participants underwent cerebral magnetic resonance imaging, cognitive testing and had blood brain injury markers analyzed. Whilst cognitive performance and biochemical markers were largely unaffected, morphological magnetic resonance imaging changes were evident. These results may pave the way for future translational studies of the therapeutic potential of hypoxia in neurodegenerative diseases.